THE RELATIONSHIP BETWEEN WAIST-HIP RATIO AND 60-METER RUNNING SPEED Studies on students of the Faculty of Medicine, Diponegoro University - Niken Ayu Dewi Masitoh; Hardhono Susanto; Endang Kumaidah; Yuswo Supatmo (JURNAL KEDOKTERAN DIPONEGORO (DIPONEGORO MEDICAL JOURNAL), 2022)
It is imperative to improve Indonesia's achievement in sprint category using an indicator according to talent scouting. The running speed of those with excessive body fat is slower. The distribution of body fat, especially in the area of abdomen and hip, could be measured using the waist hip ratio indicator. This study is aimed at determining the relationship between waist-hip ratio and 60-m running speed. This was a cross-sectional study. The subjects were chosen using simple random sampling. There were 32 medical students of Diponegoro University that met the inclusion criteria and did not meet the exclusion criteria.. The subjects were measured for their waist circumference, hip circumference, leg length, and 60-m running speed. The mean of waist hip ratio was 0.88 ± 0.07; the mean of leg length was 80.24 ± 3.75 cm; the mean of 60-m running speed was 5.49 ± 0.69 m/ s. Pearson correlation test between waist-hip ratio and 60-m running speed of Diponegoro University's medical students showed a significant negative correlation (r= -0.515; p= 0.003). According to multiple linear regression analysis, it was found that waist-hip ratio affected 60-m running speed as much as 26.6%. (R2= 0.266). Thus, there is a significant negative correlation between waist-hip ratio and 60-m running speed.Keywords: waist-hip ratio, 60-m running speed